The adventures of a forty-niner. An historic description of California, with events and ideas of San Francisco and its people in those early days. - Knower, Daniel (Albany, Weed-Parsons printing co., 1894)
An Albany, New York, physician, Daniel Knower (b. ca. 1818) sailed for California in 1849 with twelve prefabricated frame houses for the San Francisco market. The adventures of a forty-niner (1894) describes Knower's business and real estate speculations in San Francisco as well as an extended visit to a mining camp near Coloma and the life of prospectors there.
Spine title: The days of the forty-niners.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Gold discoveries; California -- Description and travel; San Francisco (Calif.) -- History; Urbanization -- California; Real estate development -- California; Business -- California